(untitled) (Cadernos de Ética e Filosofia Política, 2015)
This paper aims at explaining the Viconian defense of civil life through the constitution of his “The New Science” (Nuova Scienza) and his understanding of civil world origins. This text will consider the metaphysical reflection set off in “On the most ancient wisdom of the Italians” (De antiquíssima), which gains a broader meaning in “Universal right” (Diritto Universale). In this work, Vico seeks the foundations of human civility’s wisdom by studding law science. These foundations are synthesized into a proposition of a nova scientia tentatur. In its closing remarks this paper presents the Viconian conceptualization of a new wisdom based on the liaison between Philology and Philosophy.